2016
DOI: 10.5009/gnl15364
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying Endoscopy with Narrow Band Imaging of Early Gastric Cancer: Correlation with Histopathology and Mucin Phenotype

Abstract: Background/AimsMagnifying endoscopy with narrow band imaging (ME-NBI) is a useful modality for the detailed visualization of microsurface (MS) and microvascular (MV) structures in the gastrointestinal tract. This study aimed to determine whether the MS and MV patterns in ME-NBI differ according to the histologic type, invasion depth, and mucin phenotype of early gastric cancers (EGCs).MethodsThe MS and MV patterns of 160 lesions in 160 patients with EGC who underwent ME-NBI before endoscopic or surgical resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…If irregular microvascular and/or microsurface patterns are observed, a diagnosis of gastric cancer can be made [34, 43]. Some studies verified that NBI microvascular and/or microsurface patterns can also predict the histologic type of early gastric cancer (differentiated or undifferentiated) [10, 34, 44, 45]. …”
Section: Stomachmentioning
confidence: 99%
“…If irregular microvascular and/or microsurface patterns are observed, a diagnosis of gastric cancer can be made [34, 43]. Some studies verified that NBI microvascular and/or microsurface patterns can also predict the histologic type of early gastric cancer (differentiated or undifferentiated) [10, 34, 44, 45]. …”
Section: Stomachmentioning
confidence: 99%
“…However, no studies have reported the difference between EGCs of the corpus and antrum under ME-NBI. The MV and MS features of EGC summarized in previous studies also cannot be used to distinguish between the different regions of antrum and corpus [13,[15][16][17][18]. We hypothesize that there may be different MV and MS patterns between EGCs of the corpus and antrum under ME-NBI.…”
Section: Introductionmentioning
confidence: 81%
“…The MV patterns were classi ed as loop, ne network, or corkscrew according to the classi cation previously reported [16] (Fig. 2).…”
Section: Me-nbimentioning
confidence: 99%
“…ME-NBI is a powerful diagnostic modality because it can enable visualization of real-time microscopic images of the mucosal surface 9 , and the most advanced endoscope has a maximal resolution power as small as 6.4 ”m 10 . Although the clinical usefulness of ME-NBI has been reported in gastritis and early gastric cancer 11 12 , reports on use of ME-NBI in gastric subepithelial lesions are few. Histologically, heterotopic pancreas mainly consists of exocrine tissue and excretory ducts.…”
Section: Discussionmentioning
confidence: 99%